Social organizations and habitat self-management in neoliberal urban contexts - María Carla Rodríguez; María Cecilia Zapata (Íconos)
This article analyzes the characteristics and effects of the execution of the Housing Self-Management Program (Law No. 341/00) in the City of Buenos Aires from the beginning of the century to the present and the historiographic course of the dispute for the centrality of the popular sectors in this policy. To accomplish this task, the article problematizes the relationship between self-management and the right to the city based on the identification of opportunity and limitation frames present in a neoliberal context. Mixed methods were used in this research and primary sources and the results of the doctoral theses of the authors, which involved a survey of 120 cooperative members of the Program executed in 2018, were recovered. A sample created for this study covered 60% of the total families inhabiting the areas were the Law 341 was applied. Through this research, it was apparent that self-management was configured as an enabler of popular sectors seeking to inhabit urban central spaces. Self-management was simultaneously disputed due to its implications and openness in terms of reorganization prospects for the founding relationships of the capitalist social order.